2005
DOI: 10.1037/0022-3514.88.2.304
|View full text |Cite
|
Sign up to set email alerts
|

Assortative Mating and Marital Quality in Newlyweds: A Couple-Centered Approach.

Abstract: Using a couple-centered approach, the authors examined assortative mating on a broad range of variables in a large (N = 291) sample of newlyweds. Couples showed substantial similarity on attitude-related domains but little on personality-related domains. Similarity was not due to social homogamy or convergence. The authors examined linear and curvilinear effects of spouse similarity on self and observer indicators of marital quality. Results show (a) positive associations between similarity and marital quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
506
4
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(543 citation statements)
references
References 52 publications
27
506
4
6
Order By: Relevance
“…This was measured through their views on time spent online and through their evaluation of specific activities which might be considered problematic as regards emotional or sexual infidelity and addiction. Research about offline attitudes, values and problematic behavior has shown that married partners tend to be more similar to each other than to other people (Feng & Baker, 1994;Grant et al, 2007;Low, Cui, & Merikangas, 2007;Luo & Klohnen, 2005;Mare & Schwartz, 2006;Murray et al, 2002;Sakai et al, 2004;White & Hatcher, 1984). This paper investigated whether the same principle is valid for online behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This was measured through their views on time spent online and through their evaluation of specific activities which might be considered problematic as regards emotional or sexual infidelity and addiction. Research about offline attitudes, values and problematic behavior has shown that married partners tend to be more similar to each other than to other people (Feng & Baker, 1994;Grant et al, 2007;Low, Cui, & Merikangas, 2007;Luo & Klohnen, 2005;Mare & Schwartz, 2006;Murray et al, 2002;Sakai et al, 2004;White & Hatcher, 1984). This paper investigated whether the same principle is valid for online behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For example, neuroticism similarity was positive for female relationship quality and conscientiousness similarity was positive for male relationship quality (Luo & Klohnen, 2005). Finally, Gattis, Berns, Simpson, and Christensen (2004) studied distressed and nondistressed couples using difference score similarities.…”
Section: Similarity Effects Of Big Five Traits and Relationship Outcomesmentioning
confidence: 99%
“…Further, Luo and Klohnen (2005) tested the effect of profile similarity and difference scores on Big Five traits on observed and self-reported marital quality of both partners. The results suggest effects for agreeableness and openness for both partners' relationship quality, reflecting that if both partners were more similarly agreeable and open, self-reported and observed relationship quality was higher.…”
Section: Similarity Effects Of Big Five Traits and Relationship Outcomesmentioning
confidence: 99%
“…To calculate relative similarity (for level and 298 consistency, respectively), we first computed difference-score based similarity between the 299 female and each of the two males (bold and shy) as the absolute value of the difference in 300 the respective behaviour (e.g. Gaunt, 2006;Luo et al, 2005;Montiglio et al, 2016) between 301 the female and the bold male, and the female and the shy male. Thus, similarity (in level and 302 consistency, respectively) is highest at zero and dis-similarity increases with increasing 303 values.…”
mentioning
confidence: 99%